Sulforaphane Alleviates Particulate Matter-Induced Oxidative Stress in Human Retinal Pigment Epithelial Cells - Sim, Hyunchae; Lee, Wonhwa; Choo, Samyeol; Park, Eui Kyun; Baek, Moon-Chang; Lee, In-Kyu; Park, Dong Ho; Bae, Jong-Sup (Frontiers in Medicine, 2021)
Age-related macular degeneration (AMD) is a leading cause of blindness in the elderly, and oxidative damage to retinal pigment epithelial (RPE) cells plays a major role in the pathogenesis of AMD. Exposure to high levels of atmospheric particulate matter (PM) with an aerodynamic diameter of less than 2.5 μm (PM2.5) causes respiratory injury, primarily due to oxidative stress. Recently, a large community-based cohort study in the UK reported a positive correlation between PM2.5 exposure and AMD. Sulforaphane (SFN), a natural isothiocyanate found in cruciferous vegetables, has known antioxidant effects. However, the protective effects of SNF in the eye, especially in the context of AMD, have not been evaluated. In the present study, we evaluated the effect of SFN against PM2.5-induced toxicity in human RPE cells (ARPE-19) and elucidated the molecular mechanism of action. Exposure to PM2.5 decreased cell viability in ARPE-19 cells in a time- and dose-dependent manner, potentially due to elevated intracellular reactive oxygen species (ROS). SFN treatment increased ARPE-19 cell viability and decreased PM2.5-induced oxidative stress in a dose-dependent manner. PM2.5-induced downregulation of serum- and glucocorticoid-inducible kinase 1 (SGK1), a cell survival factor, was recovered by SFN. PM2.5 treatment decreased the enzymatic activities of the antioxidant enzymes including superoxide dismutase and catalase, which were restored by SFN treatment. Taken together, these findings suggest that SFN effectively alleviates PM2.5-induced oxidative damage in human ARPE-19 cells via its antioxidant effects, and that SFN can potentially be used as a therapeutic agent for AMD, particularly in cases related to PM2.5 exposure.